THE EFFECT OF DIFFERENT SALINITY ON THE SURVIVAL OF VANAME SHRIMP (Litopenaeus vannamei) SIZE PL8-12 IN EXPERIMENTAL TANK - Rizal, Mohammad; Muhajir, Muhajir; Sumaryam, Sumaryam (Universitas Mataram, 2025)
Vaname shrimp (Litopenaeus vannamei) seed production fluctuates and naturally, seasonal factors are one of the causes. The rainy season causes sea water salinity to tend to decrease, whereas the dry season causes sea water salinity to tend to increase. Physiologically, the dynamics of salinity can influence the survival of vaname shrimp seeds and the process is regulated through osmoregulation, namely the response to regulating osmotic pressure between body fluids and the aquatic environment. This study used an experimental method with Completely Randomized Design (CRD) with 4 salinity treatments and 6 replications. The salinity tested included 27 ppt (treatment A), 29 ppt (treatment B), 31 ppt (treatment C), and 33 ppt (treatment D). The test animals for this study used whiteleg shrimp (Litopenaeus vannamei) size PL8-12 with an average weight of 0.001 g/individual. The stocking density was 15 individuals/liter and the maintenance media was a mixture of seawater and freshwater with a total volume of 3 liters/tank. The results showed that treatment D produced the best effect for the survival of whiteleg shrimp (Litopenaeus vannamei) size PL8-12 of 98.5%. Water quality data obtained from acidity levels of 8.3-8.5, temperatures ranging from 27-280C and dissolved oxygen ranging from 4.4-4.5 ppm.